Management Principles from an Islamic Perspective: Exploration of the Interpretation of the Qur'an - Nurhalimah Harahap; Atika Hanan Julia Harahap; Siti Rukhaiyah (Education Achievement: Journal of Science and Research, 2024)
This research aims to explore and analyze the managerial principles contained in the Al-Qur'an using an interpretive approach, as well as their relevance to modern managerial practice. Management, as a rapidly developing scientific discipline, is often understood from a Western perspective, while the Islamic perspective in management has not been widely explored. Through literature study and qualitative analysis of Al-Qur'an interpretations, this research identifies key principles in Islamic management, such as justice, trust, responsibility and ethical leadership. The research results show that these principles offer comprehensive and relevant guidance for resource management and leadership in the context of modern organizations. The managerial principles in the Qur'an not only provide direction in terms of strategic decisions but also emphasize the importance of the moral and spiritual dimensions in management. This research provides new insights for academics and practitioners in understanding and applying Islamic managerial principles, as well as suggesting the integration of these principles in contemporary managerial practice.